Endogenous glucocorticoid receptor signaling drives rhythmic changes in human T‐cell subset numbers and the expression of the chemokine receptor CXCR4. Issue 1 (19th September 2013) - Besedovsky, Luciana; Born, Jan; Lange, Tanja
Abstract : In humans, numbers of circulating naive T cells strongly decline in the morning, which was suggested to be mediated by cortisol, inducing a CXCR4 up‐regulation with a subsequent extravasation of the cells. As a systematic evaluation of this assumption is lacking, we investigated in two human placebo‐controlled studies the effects of the glucocorticoid receptor (GR) antagonist mifepristone (200 mg orally at 23:00) and of suppressing endogenous cortisol with metyrapone (1 g orally at 04:00) on temporal changes in CXCR4 expression and numbers of different T‐cell subsets using flow cytometry. Mifepristone attenuated, and metyrapone completely blocked, the morning increase in CXCR4 expression on naive T cells. In parallel, both substances also hindered the decline in naive T‐cell numbers with this effect, however, being less apparent after mifepristone. We identified, and confirmed in additional in vitro studies, a partial agonistic GR effect of mifepristone at night ( i.e., between 02:00 and 03:30) that could explain the lower antagonistic efficacy of the substance on CXCR4 expression and naive T‐cell counts. CXCR4 expression emerged to be a most sensitive marker of GR signaling. Our studies jointly show that endogenous cortisol, specifically via GR activation, causes the morning increase in CXCR4 expression and the subsequent extravasation of naive T cells, thus revealing an important immunological function of the morning cortisol rise.—Besedovsky, L., Born, J., Lange, T. Endogenous glucocorticoid receptor signaling drives rhythmic changes in human T‐cell subset numbers and the expression of the chemokine receptor CXCR4. FASEB J . 28, 67–75 (2014). www.fasebj.org